Liver response to low-hexachlorobenzene exposure in protein- or energy-restricted rats - Rodrigues, Maria Aparecida Marchesan [UNESP]; Sanchez-Negrette, M. [UNESP]; Mantovani, M. S. [UNESP]; Sant'ana, L. S. [UNESP]; Angeleli, A. Y O [UNESP]; Montenegro, M. R. [UNESP]; Camargo, João Lauro Viana de [UNESP] (Elsevier, 1991)
The individual effects of protein deficiency and energy restriction on liver response to low-hexachlorobenzene (HCB) exposure were investigated in adult male Wistar rats. In rats fed either the low-protein or control diet, the only effect caused by HCB was a decrease in paralysis time following an ip injection of zoxazolamine. This decrease was similar for both groups. In the animals subjected to energy restriction, HCB induced a greater decrease in paralysis time, an increase in the size of centrilobular hepatocytes, a lower liver DNA content and an increased concentration of HCB in the adipose tissue, compared with the control and protein-deficient groups. Our data suggest that energy restriction increases liver response to HCB, while protein deficiency does not impair the hepatic reaction to small doses of HCB exposure.
Keywords: hexachlorobenzene; adipose tissue; animal experiment; energy; liver toxicity; male; nonhuman; paralysis; priority journal; protein deficiency; rat; Administration, Oral; Animal; Body Weight; Dietary Proteins; Energy Intake; Hexachlorobenzene; Liver; Male; Organ Weight; Paralysis; Rats; Rats, Inbred Strains; Support, Non-U.S. Gov't; Tissue Distribution